Facebook as a collaborative and communication tool: A study of secondary school students in Malaysia - Raman, Arumugam; Mohd Sani, Ruuhina; Karpal Singh, Paramjit Kaur (Elsevier Ltd., 2014)
This study discusses the acceptance of the utilization of Facebook as a communication tool and collaborative educational tool amongst secondary school students.This study is based on the four constructs of the Unified Theory of Acceptance and Use of Technology.The respondents were 150 secondary school students who were randomly selected. The data for this study was elicited through questionnaires adapted from Venkatesh et al. (2003). The findings showed that performance expectations and effort expectations do not have a significant positive impact on behavioral intentions.On the other hand, the coefficients for social influence and facilitating conditions had a significant positive effect on behavioral intentions.